2012
DOI: 10.1002/humu.22165
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Clinical and Molecular Analysis of 12 Families with Type 1 Recessive Cutis Laxa

Abstract: Autosomal recessive cutis laxa type I (ARCL type I) is characterized by generalized cutis laxa with pulmonary emphysema and/or vascular complications. Rarely, mutations can be identified in FBLN4 or FBLN5. Recently, LTBP4 mutations have been implicated in a similar phenotype. Studying FBLN4, FBLN5 and LTBP4 in 12 families with ARCL type I, we found bi-allelic FBLN5 mutations in 2 probands, whereas 9 probands harbored biallelic mutations in LTBP4. FBLN5 and LTBP4 mutations cause a very similar phenotype associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 40 publications
2
68
1
Order By: Relevance
“…Callewaert et al and other investigators have reported pulmonary emphysema and vascular complications as two main characteristics of ARCL type I (10,11). However, our case with the novel homozygous mutation has limited segments, with pulmonary emphysema and no vascular involvement.…”
Section: Discussioncontrasting
confidence: 48%
“…Callewaert et al and other investigators have reported pulmonary emphysema and vascular complications as two main characteristics of ARCL type I (10,11). However, our case with the novel homozygous mutation has limited segments, with pulmonary emphysema and no vascular involvement.…”
Section: Discussioncontrasting
confidence: 48%
“…FBLN5 knockout mice survive to adulthood but develop pronounced elastinopathy with human aging phenotypes like loose skin, vascular abnormalities, severe emphysema and genital prolapse 15 16. This phenotype in mice is very similar to the human connective tissue disorder cutis laxa, which can be caused by mutations in FBLN5 and is often associated with severe emphysema 19. Based on these findings we consider FBLN5 as a potential novel player in tissue repair in COPD and decided to further focus on this gene.…”
Section: Discussionmentioning
confidence: 94%
“…In two patients with ALDH18A1-related CL, kinky tortuosity of brain vessels was reported [16,17] demonstrating that in this severe form of CL vessels are especially vulnerable. Therefore, vessels should not only be assessed in ADCL, ARCL1, and ATS that are well known for their arterial malformations [1,18,19], but also in proline biosynthesis pathologies.…”
Section: Discussionmentioning
confidence: 99%